MONITORING OF IMPLEMENTING OF E-GOVERNANCE TOOLS IN LOCAL GOVERNMENT: SURVEY RESULTS OF 2015 - А.О.Serenok (Pressing Problems of Public Administration, 2016)
The results of monitoring the of cial web-sites of local governments in 125 of the largest cities of Ukraine have been analyzed to evaluate their informative contents, a degree of local governments’ preparedness for a transparent presentation of their decision-making activities, use of feedback tools, administrative service delivery, an extent of their data update, and web-site user-friendliness.